Physical properties of the Bi1.5Zn0.92-2xHfxNb1.5O6.92 solid solutions - (:unkn) unknown (ELSEVIER SCI LTD, 2016)
The Hf doping effect on the structural, compositional, optical, electrical and dielectric properties of the bismuth-zinc-niobium oxide pyrochlore ceramics is explored by means of scanning electron microscopy, energy dispersive X-ray spectroscopy, ultraviolet-visible light spectroscopy in the wavelength range of 200-1100 nm, temperature dependent electrical resistivity measurements in the range of 300-460 K and dielectric spectroscopy in the frequency range of 0.1-1.0 GHz. The optimum solubility limit in the Bi1.5Zn0.92-2xHfxNb1.5O6.92 solid solution is observed for the Hf content of 0.06. Increasing the Hf content from 0.03 to 0.06 decreased the room temperature, lattice constant, strain, dislocation density, optical energy band gap and electrical resistivity. It also increased the crystallite size and the dielectric constant. The energy band gap of the pure BZN (3.30 eV) decreased to 2.21 and reached 2.10 eV as the Hf content increased from 0.03 to 0.06. This behavior of the BZN suggests its suitability for optical applications of the visible region of light like photovoltaic devices. In addition, the remarkable increase in the dielectric constant from 258 to 280 and 456 nominates the Hf doped pyrochlore for passive mode operation devices like microwave capacitors. (C) 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Electron microscopy; Powder metallurgy; Ceramics; X-ray scattering; OPTICAL-PROPERTIES; CONDUCTION